SARS-CoV-2 in a stream running through an underprivileged, underserved, urban settlement in São Paulo, Brazil: A 7-month follow-up. (1st December 2021) - Pepe Razzolini, Maria Tereza; Funada Barbosa, Mikaela Renata; Silva de Araújo, Ronalda; Freitas de Oliveira, Ivo; Mendes-Correa, Maria Cássia; Sabino, Ester C.; Garcia, Suzi Cristina; de Paula, Anderson V.; Villas-Boas, Lucy S.; Costa, Silvia Figueiredo; Dropa, Milena; Brandão de Assis, Denise; et al.
Abstract: COVID-19 pandemic has led to concerns on the circulation of SARS-CoV-2 in the environment, its infectivity from the environment and, the relevance of transmission via environmental compartments. During 31 weeks, water samples were collected from a heavily contaminated stream going through an urban, underprivileged community without sewage collection. Our results showed a statistically significant correlation between cases of COVID-19 and SARS in the community, and SARS-CoV-2 concentrations in the water. Based on the model, if the concentrations of SARS-CoV-RNA (N1 and N2 target regions) increase 10 times, there is an expected increase of 104% [95%CI: (62–157%)] and 92% [95%CI: (51–143%)], respectively, in the number of cases of COVID-19 and SARS. We believe that differences in concentration of the virus in the environment reflect the epidemiological status in the community, which may be important information for surveillance and controlling dissemination in areas with vulnerable populations and poor sanitation. None of the samples were found infectious based cultures. Our results may be applicable globally as similar communities exist worldwide. Graphical abstract: Image 1 Highlights: A follow-up in an urban settlement stream showed high concentration of SARS-CoV-2. COVID-19 and severe cases were correlated with virus concentrations. Water samples were culture-negative; suggesting virus is not infectious. Environmental monitoring may be useful to track the spread of COVID-19.